Pastukh I. M., Sokolova G. N. Energetic preconditions of nitriding in a glowing discharge with independent parameters. - Пастух, И.М.; Соколова Г.Н., Г.Н. (Problems of Tribology, 2014)
An analysis is conducted on the energetic effects from the process of nitriding in a glowing discharge with a follow up of perspectives on the applications of related technological modes with independent parameters.